21st Century Learning: Is ICT Really Integrated In EFL Classroom or Merely Segregated Outside The Classroom? - Ririn Ovilia; Risda Asfina (Universitas Merdeka Malang, 2017)
In 21st century, along with the rapid development of technology, the teachers begin to involve Information and Communication Technology (ICT) in EFL learning. However, the question is, “is the use of ICT really integrated or merely segregated outside the classroom?” This study was intended to answer that question. It was a case study which attempted to see the practice of integrating ICT in EFL classroom, particularly in Charis School―a private Junior High School in Malang, and to investigate the teacher’s perceptions toward the integration of ICT in the learning process. Charis School was selected as the research setting since it met the criteria regarding the integration of ICT in EFL classroom: the ICT accessibility, teacher’s ICT competence and institutional supports. The instruments were interview guide and observation sheet. The results of this study showed that the teacher was aware of the integration of ICT in EFL classroom and she integrated it in the instruction and activities in the learning process.